The Implementation Of Teams Game Tournament (TGT) To Improve Students’ Writing Ability Of Second Grade Students In SMP Negeri 7 Padang - Ananda Feby; Dania Rahma; Suparmi Suparmi (Simpati, 2024)
This study aimed to determine whether the implementation of the Teams Game Tournament (TGT) can improve students’ writing abilities in learning English of second grade students in SMP Negeri 7 Padang. The population was second grade students in SMP Negeri 7 Padang. The sample of this research was 33 students of VIII.5 class. This type of research was quantitative. The method used was a pre-experimental design, with one group pre-test and post-test. The result of the data showed that the average students score on the post-test was (89,45) higher that the average score on the pre-test (60.24). From the t-test, the study showed that the t-test value (11,54) is higher that t-table (1,697) at a significance level of 0,05 with degree freedom (df) = 32. This result meant that there was a significant difference. This indicated that the alternative hypothesis (H1) was accepted and the nul hypothesis (H0) was rejected. Hence, it can be concluded that the implementation of Teams Game Tournament (TGT) significantly improve students’ writing ability.